Mitochondrial dysfunction in Alzheimer's disease - a proteomics perspective. (3rd April 2021) - Abyadeh, Morteza; Gupta, Vivek; Chitranshi, Nitin; Gupta, Veer; Wu, Yunqi; Saks, Danit; Wander Wall, Roshana; Fitzhenry, Matthew J.; Basavarajappa, Devaraj; You, Yuyi; Salekdeh, Ghasem H; Haynes, Paul a; et al.
ABSTRACT: Mitochondrial dysfunction is involved in Alzheimer's disease (AD) pathogenesis. Mitochondria have their own genetic material; however, most of their proteins (∼99%) are synthesized as precursors on cytosolic ribosomes, and then imported into the mitochondria. Therefore, exploring proteome changes in these organelles can yield valuable information and shed light on the molecular mechanisms underlying mitochondrial dysfunction in AD. Here, we review AD-associated mitochondrial changes including the effects of amyloid beta and tau protein accumulation on the mitochondrial proteome. We also discuss the relationship of ApoE genetic polymorphism with mitochondrial changes, and present a meta-analysis of various differentially expressed proteins in the mitochondria in AD. Area covered : Proteomics studies and their contribution to our understanding of mitochondrial dysfunction in AD pathogenesis. Expert opinion : Proteomics has proven to be an efficient tool to uncover various aspects of this complex organelle, which will broaden our understanding of mitochondrial dysfunction in AD. Evidently, mitochondrial dysfunction is an early biochemical event that might play a central role in driving AD pathogenesis.